Identification of the Vasoconstriction-Inhibiting Factor (VIF), a Potent Endogenous Cofactor of Angiotensin II Acting on the Angiotensin II Type 2 Receptor. Issue 16 (21st April 2015) - Salem, Silvia; Jankowski, Vera; Asare, Yaw; Liehn, Elisa; Welker, Pia; Raya-Bermudez, Ana; Pineda-Martos, Carmen; Rodriguez, Mariano; Muñoz-Castañeda, Juan Rafael; Bruck, Heike; Marx, Nikolaus; Machado, Fernanda B.; et al.
<x xml:space="preserve">Abstract</x> Background— The renin-angiotensin system and especially the angiotensin peptides play a central role in blood pressure regulation. Here, we hypothesize that an as-yet unknown peptide is involved in the action of angiotensin II modulating the vasoregulatory effects as a cofactor. Methods and Results— The peptide with vasodilatory properties was isolated from adrenal glands chromatographically. The effects of this peptide were evaluated in vitro and in vivo, and the receptor affinity was analyzed. The plasma concentration in humans was quantified in patients with chronic kidney disease, patients with heart failure, and healthy control subjects. The amino acid sequence of the peptide from bovine adrenal glands was HSSYEDELSEVL EKPNDQAE PKEVTEEVSSKDAAE, which is a degradation product of chromogranin A. The sequence of the peptide isolated from human plasma was HSGFEDELSEVLENQSSQAELKEAVEEPSSKDVME. Both peptides diminished significantly the vasoconstrictive effect of angiotensin II in vitro. Therefore, we named the peptide vasoconstriction-inhibiting factor (VIF). The vasoregulatory effects of VIF are mediated by the angiotensin II type 2 receptor. VIF impairs angiotensin II–induced phosphorylation of the p38 mitogen-activated protein kinase pathway but not of extracellular-regulated kinase 1/2. The vasodilatory effects were confirmed in vivo. The plasma concentration was significantly increased in renal patients and patients with heart failure. Conclusions— VIF is a vasoregulatory peptide that modulates the vasoconstrictive effects of angiotensin II by acting on the angiotensin II type 2 receptor. It is likely that the increase in VIF may serve as a counterregulatory effect to defend against hypertension. The identification of this target may help us to understand the pathophysiology of renal and heart failure and may form a basis for the development of new strategies for the prevention and treatment of cardiovascular disease.